Interprofessional Consensus Regarding Design Requirements for Liquid-Based Perinatal Life Support (PLS) Technology - van der Hout-van der Jagt, M. Beatrijs; Verweij, E. J. T.; Andriessen, Peter; de Boode, Willem P.; Bos, Arend F.; Delbressine, Frank L. M.; Eggink, Alex J.; Erwich, Jan Jaap H. M.; Feijs, Loe M. G.; Groenendaal, Floris; Kramer, Boris W. W.; Lely, A. Titia; et al. (Frontiers in Pediatrics, 2022)
Liquid-based perinatal life support (PLS) technology will probably be applied in a first-in-human study within the next decade. Research and development of PLS technology should not only address technical issues, but also consider socio-ethical and legal aspects, its application area, and the corresponding design implications. This paper represents the consensus opinion of a group of healthcare professionals, designers, ethicists, researchers and patient representatives, who have expertise in tertiary obstetric and neonatal care, bio-ethics, experimental perinatal animal models for physiologic research, biomedical modelling, monitoring, and design. The aim of this paper is to provide a framework for research and development of PLS technology. These requirements are considering the possible respective user perspectives, with the aim to co-create a PLS system that facilitates physiological growth and development for extremely preterm born infants.